2022
DOI: 10.1155/2022/7179477
|View full text |Cite
|
Sign up to set email alerts
|

Land Resource Use Classification Using Deep Learning in Ecological Remote Sensing Images

Abstract: Aiming at the problems that the traditional remote sensing image classification methods cannot effectively integrate a variety of deep learning features and poor classification performance, a land resource use classification method based on a convolutional neural network (CNN) in ecological remote sensing images is proposed. In this study, a seven-layer convolution neural network is constructed, and then the two fully connected layer features of the improved CNN network training output are fused with the fifth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Abdullah and others [31] found that red-edge spectral data were beneficial in detecting green attacks in trees. This study did not directly assess the attack stage, but future research could address this using PCA and training data from plot-level surveys to build neural network models to classify vegetation threats [22,32]. Early identification of tree stress would allow for mitigating measures to be taken to prevent the further spread of SPB in a forest [11].…”
Section: Discussionmentioning
confidence: 99%
“…Abdullah and others [31] found that red-edge spectral data were beneficial in detecting green attacks in trees. This study did not directly assess the attack stage, but future research could address this using PCA and training data from plot-level surveys to build neural network models to classify vegetation threats [22,32]. Early identification of tree stress would allow for mitigating measures to be taken to prevent the further spread of SPB in a forest [11].…”
Section: Discussionmentioning
confidence: 99%
“…16.09. The map comprises 12 categories, including bamboo forests, bare lands, water bodies, urban regions, paddy fields, croplands, grasslands, deciduous broad-leaf forests, deciduous needle-leaf forests, evergreen broad-leaf forests, and solar panels [ 16 ]. For this study, bamboo forests, deciduous broad-leaf forests, deciduous needle-leaf forests, and evergreen broad-leaf forests are merged into one class and categorized as forests.…”
Section: Methodsmentioning
confidence: 99%
“…It is proven that the results of research using a remote sensing approach can produce reliable data. In addition, it is about classifying land resources using deep learning (Xia et al, 2022).…”
Section: Figure 1 Bibliometric Keyword Analysis Graphmentioning
confidence: 99%